Case-Smith's occupational therapy for children and adolescents - O'Brien, Jane Clifford, ....-; Kuhaneck, Heather, ....- (St. Louis (Mo) : Elsevier, 2020)
The number one book in pediatric OT is back! Focusing on children from infancy to adolescence, Case-Smith's Occupational Therapy for Children and Adolescents, 8th Edition provides comprehensive, full-color coverage of pediatric conditions and treatment techniques in all settings. Its emphasis on application of evidence-based practice includes: eight new chapters, a focus on clinical reasoning, updated references, research notes, and explanations of the evidentiary basis for specific interventions. Coverage of new research and theories, new techniques, and current trends, with additional case studies, keeps you in-step with the latest advances in the field. Developmental milestone tables serve as a quick reference throughout the book! NEW! Eight completely new chapters cover Theory and Practice Models for Occupational Therapy With Children, Development of Occupations and Skills From Infancy Through Adolescence, Therapeutic Use of Self, Observational Assessment and Activity Analysis, Evaluation Interpretation, and Goal Writing, Documenting Outcomes, Neonatal Intensive Care Unit, and Vision Impairment. NEW! A focus on theory and principles Practice Models promote clinical reasoning. NEW! Emphasis on application of theory and frames of reference in practice appear throughout chapters in book. NEW! Developmental milestone tables serve as quick reference guides. NEW! Online materials included to help facilitate your understanding of what's covered in the text. NEW! Textbook is organized into six sections to fully describe the occupational therapy process and follow OTPF.
Keywords: Ergotherapie